Vestigium strategy for the development of research skills in undergraduates, Chiclayo 2016 - Castañeda Quiroz, Selfa Obdulia (2017)
This present article is an abstract of a thesis, which aims to propose the Vestigium Strategy for development of research skills in Cesar Vallejo University (UCV) Undergraduate students. The research was carried out on the basis of the application of the survey to a representative sample of students from higher-level studies. The obtained results were analyzed and discussed at the light of recent educational theories on teaching and learning subject of scientific research, where the most important results were: i) Insufficient research training in the regular basic education; ii) The willingness of UCV students to recognize the importance of research in the university life; iii) Being important, the limitations of students to carry out the research was identified; iv) The ideal profile of researcher was determined; v) The high and low point of the teaching-learning process in UCV were identified. The proposed strategy has as methodological basis: i) To encourage the development of a student profile who is socially responsible; ii) To encourage the development of a researcher profile in professors at UCV, which is to have rational, flexible, and respectful interpersonal nature (democratic) to guide the student-researcher to the innovation not to perfection iii) To update the investigative development with the latest trends, promoting a style of free, open and inclusive research.